Optimalisasi Nilai Tambah (Value-Added) Produk Peternakan melalui Diversifikasi Olahan Telur Asin - Rohmatul Anwar; Diah Reni Asih; Miftahuddin Ahmad; Dwi Subakti Prasetyo (Universitas Pahlawan Tuanku Tambusai, 2026)
Duck eggs are a highly nutritious food source, yet they suffer from drawbacks such as rapid spoilage and a strong, fishy odor. This community service project, conducted in Tanjung Inten Village, East Lampung, aimed to teach processing techniques for salted eggs featuring spicy and aromatic (garlic) flavor variants, thereby extending shelf life and enhancing economic value. Carried out in April 2026, the initiative employed a combination of theoretical instruction and hands-on practice with a group of local housewives. The training demonstrated that the community successfully grasped and implemented innovative, clean, and hygienic methods for producing salted eggs. Incorporating herbal seasonings into the brine solution proved effective in extending the duck eggs' shelf life to up to nine weeks. Furthermore, the blend of garlic and chili successfully eliminated the fishy odor, imparted a desirable grainy texture to the yolk, and alleviated community concerns regarding cholesterol. This innovative product also generated added value, offering the potential for increased profits for the producers.